Innate Immune Response of Human Embryonic Stem Cell-Derived Fibroblasts and Mesenchymal Stem Cells to Periodontopathogens - Gopu Sriram; Vaishali Prakash Natu; Intekhab Islam; Xin Fu; Chaminda Jayampath Seneviratne; Kai Soo Tan; Tong Cao (Hindawi Limited, 2016)
Periodontitis involves complex interplay of bacteria and host immune response resulting in destruction of supporting tissues of the tooth. Toll-like receptors (TLRs) play a role in recognizing microbial pathogens and eliciting an innate immune response. Recently, the potential application of multipotent stem cells and pluripotent stem cells including human embryonic stem cells (hESCs) in periodontal regenerative therapy has been proposed. However, little is known about the impact of periodontopathogens on hESC-derived progenies. This study investigates the effects of heat-killed periodontopathogens, namely, Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans, on TLR and cytokine expression profile of hESC-derived progenies, namely, fibroblasts (hESC-Fib) and mesenchymal stem cells (hESC-MSCs). Additionally, the serotype-dependent effect of A. actinomycetemcomitans on hESC-derived progenies was explored. Both hESC-Fib and hESC-MSCs constitutively expressed TLR-2 and TLR-4. hESC-Fib upon exposure to periodontopathogens displayed upregulation of TLRs and release of cytokines (IL-1β, IL-6, and IL-8). In contrast, hESC-MSCs were largely nonresponsive to bacterial challenge, especially in terms of cytokine production. Further, exposure of hESC-Fib to A. actinomycetemcomitans serotype c was associated with higher IL-8 production than serotype b. In contrast, the hESC-MSCs displayed no serotype-dependent response. Differential response of the two hESC progenies implies a phenotype-dependent response to periodontopathogens and supports the concept of immunomodulatory properties of MSCs.